Modest sex differences in the test of basic auditory capabilities (TBAC) - McFadden, Dennis; Pasanen, Edward G.; Kidd, Gary R.; Gygi, Brian (Frontiers in Psychology, 2024)
The Test of Basic Auditory Capabilities (TBAC) consists of 19 discrimination and identification tasks selected to study individual differences in audition. In one TBAC study, performance was measured for 340 normal-hearing subjects, but no investigation into possible sex differences was undertaken. That dataset now has been re-analyzed by sex. An effect size for sex difference was calculated for each subtest, and a resampling technique was used to estimate an implied significance for each of those effect sizes. Because almost all the differences observed were small, only the basic outcomes are described here, with more detail provided in an online supplement. Peripheral physiological measures such as otoacoustic emissions exhibit larger auditory sex differences than do auditory behavioral measures, revealing that those peripheral physiological differences do not propagate simply up the auditory chain.